Evaluación del proceso de elaboración de pan fortificado tipo campesino con borojó (Borojoa Patinoi Cuatrec) y proteína de soya (Glycinemax ) en el cantón Quevedo - Acevedo Guillcatanda, Néstor Orlando (2014)
The advancement in the technology of food processing is taking other levels such as food fortification either by replacement or refund these, using new components that complement optimal nutritional value for human consumption . In the canton Quevedo have surplus agro raw material such as borojó (Borojoa patinoi cuatrec ) and soy protein ( Glycinemax ) , this was one of the indicators for this research. . Making interactions % pulp borojó levels between 2 and 3%, and 20 and 30 % soy protein at the time of the mass, which was evaluated with the fermentation time ranges from 40 min to 60 min and baking time and temperature were 30 min at 160 ° C and 50 min at 140 ° C to indicate how it interacts when making bread. Using measurement variables for weight, moisture, pH and especially the latter protein indicates if the finished product was fortified product ranges. Using technology in line with regulations NTE INEN94:1979.95,96 which indicate the levels to follow in making bread using BPM and Codex Alimentarius which guaranteed us the finished product, the same as we evaluate the organoleptic levels which helped us to know which one has more acceptability….